DAMPAK KEPESERTAAN KELAS IBU HAMIL TERHADAP PENGETAHUAN TANDA BAHAYA KEHAMILAN DI DESA CIKEAS - ida nuraida (NHM PRESS, 2022)
Knowledge of mothers on the danger of pregnancy in the village Cikeas Bogor Regency Year 2019. The population of this research is all expectant mothers in Cikeas village in 2019, which is as many as 86 pregnant mothers with sampling techniques using sampling purposive samples. Research results Most of the respondents had knowledge of the danger signs in pregnancy in the category of less, which is 50 people (58.1%) And respondents with a good knowledge of the pregnancy danger sign as much as 36 people (41.9%), most of the respondents had never participated in a pregnant women's class of 55 people (63.9%), while having attended the pregnant women's class of 31 (36.1%), there was an influence between the participation of expectant mothers in the mother class with a knowledge of hazard signs in pregnancy with the value of P value 0.000 and OR 7.159 (2,674-19,163). Based on these results can be concluded there is an influence between the membership of pregnant women in the mother class with the knowledge of danger signs in pregnancy. Advice village, Puskesmas and midwives can further socialize the class program of pregnant women to the community, so that all expectant mothers can follow the class of pregnant women